2-[3-(2-Pyridyl)pyrazin-2-yl]pyridinium tetrachloridoaurate(III) - Vahid Amani; Vickie McKee; Nasser Safari; Mehmet Akkurt; Sema Öztürk Yıldırım (Acta Crystallographica Section E, 2009)
In the anion of the title compound, (C14H11N4)[AuCl4], the AuIII atom has an almost perfect square-planar coordination. In the crystal structure, an intramolecular N—H...N and intermolecular C—H...Cl hydrogen bonds are observed. In addition, there is also a ring–metal interaction between the pyrazine ring and the AuIII atom; the distance between the centroid of the pyrazine ring and the AuIII atom is 3.628 (2) Å.